A Research of Methamphetamine Induced Psychosis in 1,430 Individuals With Methamphetamine Use Disorder: Clinical Features and Possible Risk Factors - Gan, Hong; Zhao, Yan; Jiang, Haifeng; Zhu, Youwei; Chen, Tianzhen; Tan, Haoye; Zhong, Na; Du, Jiang; Zhao, Min (Frontiers in Psychiatry, 2018)
Background and Aims: Methamphetamine (MA) abuse is commonly associated with the development of psychotic symptoms. The predictors and related risk factors of MA induced psychosis (MIP) are poorly understood. We investigated the occurrence of ATS induced psychosis, and analysed the clinical features and related risk factors among individuals with methamphetamine use disorder. Method: 1430 participants with methamphetamine use disorder were recruited from compulsory rehabilitation centers in Shanghai. A structured questionnaire including demographic characteristics, drug use history, visual analog scales, Beck Depression Inventory-13 (BDI-13) and Hamilton anxiety scale-14 (HAMA-14) were used to collect clinical related information. 56 participants had accomplished the test of CogState Battery. Results: Among the 1430 individuals with MA use disorder, 37.1% were diagnosed as MA induced psychosis according DSM-IV. There were significant differences in age, marital status, age of drug use onset, MA use years, Average MA use dose, interval of MA use, maximum dose, concurrent use of alcohol and other drugs, VAS score, MA dependence, BDI-13 scores, HAMA-14 scores, verbal learning memory, and visual learning memory between the MIP group and the none MIP group (P<0.05). The age of drug use onset (OR=0.978, p=0.011), average drug use dose (OR=1.800, p=0.015), craving score (OR=1.069, p=0.031), MA dependence (OR=2.214, p<0.001), and HAMA scores (OR=1.028, p<0.001) were associated to MIP. Conclusion: Individuals with MIP had more severe drug use problems, emotional symptoms and cognitive impairment. Earlier onset of drug use, higher quantity of drug use, higher craving, middle or severe drug use disorder and more anxiety symptoms may be related risk factors of MIP.